Gestão pública compartilhada: o caso do programa de melhoria do ensino de ciências e matemática - Pró-ciências - Lira, Luiz Alberto Rocha de (2003)
This paper is a follow up of the study of the evolution of the public policies for education, especially in the areas of improvement in the science and mathematics program, whose main purpose is to qualify teachers is these disciplines. The evaluation of strategies adopted by the Department of education for the implementation and development of the program in the states, which, on a decentralized bases and through its administrative structure is responsible for contracting higher Education Institutions in charge of preparatory courses. It discusses the enforcement of such a strategy and analyses the combined efforts between the federal sphere, represented by the coordination of preparatory courses for Higher Education Personnel (CAPES) and the Departments of Education, Science and Technology of the states, Research Spowsoring Foundations and the Federal Universities, breaking with some governmental traditions. It analyses the greater degree of interaction between the curriculum for public schools and the developments achieved in the many fields of knowledge. It is based on parameters in the proposals disposed by the law of the methods and fundamentals education, methods of curriculum, and national teaching standards, as well as studies carried out in the states that demand the biggest quantity of qualifying projects, trough analyses that are focused on the problems regarding science teaching in the Brazil and the format adopted in the implementation of the program.